A Fluctuating State in the Framework Compounds (Ba,Sr)Al(2)O(4) - Ishii, Yui (Sci Rep, 2016)
The structural fluctuation in hexagonal Ba(1−x)Sr(x)Al(2)O(4) with a corner-sharing AlO(4) tetrahedral network was characterized at various temperatures using transmission electron microscopy experiments. For x ≤ 0.05, soft modes of q ~ (1/2, 1/2, 0) and equivalent wave vectors condense at a transition temperature (T(C)) and form a superstructure with a cell volume of 2a × 2b × c. However, T(C) is largely suppressed by Sr-substitution, and disappears for x ≥ 0.1. Furthermore, the q ~ (1/2, 1/2, 0) soft mode deviates from the commensurate value as temperature decreases and survives in nanoscaled regions below ~200 K. These results strongly suggest the presence of a new quantum criticality induced by the soft mode. Two distinct soft modes were observed as honeycomb-type diffuse scatterings in the high-temperature region up to 800 K. This intrinsic structural instability is a unique characteristic of the framework compound and is responsible for this unusually fluctuating state.